Fermented Foods and Beverages - Anagnostopoulos, Dimitrios A.; Tsaltas, Dimitrios (My University, 2019)
Fermented foods and beverages, coming both from plants or animals, are one of the indispensable components of the intangible heritage of every community in the world, playing a crucial role in humans health, culture, and history. The use of fermentation processes comes from the ancient times by different communities all around the globe. In many cases, the fermentation process did not change at all since their first report. As a result, the tradition of the fermentation processes of many communities have passed through generations and have been reported in various documents of historical, religious, scientific, or technical context. Many different types of similar traditional fermented foods and beverages are produced with characteristic differences from region to region. Differences that most of the time are justified from local traditions, conditions, and availability of primary produce. Lactic acid bacteria and yeasts are the major groups of microorganisms associated with fermented products. The aim of this chapter is to describe traditional fermented foods and beverages from around the world, including their microbiology, their production technology, properties in nutrition, their effects in health and disease, and their future perspectives in the context as drivers of a healthy diet in view of developing innovative products.
Keywords: beverages; Fermentation; foods; microbial ecology; technology